HUBUNGAN LEVERAGE, LIKUIDITAS DAN PROFITABILITAS PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN - Yati, Norhayati (ADL ISLAMIC ECONOMIC : Jurnal Kajian Ekonomi Islam, 2023)
Food and beverage companies are companies that continue to grow. The need for food and drink is always needed by the community all the time. To meet the needs of the community, food and beverage companies must be able to compete with other companies both nationally and internationally. The purpose of this study was to determine the effect of leverage and liquidity ratios on the profitability of food and beverage manufacturing companies listed on the IDX in the 2017-2021 period. The leverage ratio is measured using the Debt to Equity Ratio (DER), the liquidity ratio is measured using the Current Ratio (CR). While Profitability is measured using Return On Equity (ROE). The population in this study were all food and beverage sub-sector manufacturing companies listed on the IDX. While the sample was selected by purposive sampling method. The research method used is multiple linear regression. The results of the study show that the Debt to Equity Ratio (DER) and Current Ratio (CR) simultaneously affect the Return On Equity (ROE). The results of multiple linear regression tests partially show that the Debt to Equity Ratio (DER) has a significant effect on Return On Equity (ROE). while the Current Ratio (CR) has no significant effect on Return On Equity (ROE).